2015
DOI: 10.1098/rsob.150064
|View full text |Cite
|
Sign up to set email alerts
|

DNA-hydrolysing activity of IgG antibodies from the sera of patients with schizophrenia

Abstract: It is believed that damage to the membranes of brain cells of schizophrenia (SCZ) patients induces the formation of autoantigens and autoantibodies. Nevertheless, the importance of immunological changes leading to the loss of tolerance to self-antigens in the genesis of SCZ has not been established. The MALDI mass spectra of the IgG light chains of 20 healthy donors were relatively homogeneous and characterized by one peak with only one maximum. In contrast to the healthy donors, the MALDI mass spectra of IgG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(77 citation statements)
references
References 56 publications
2
75
0
Order By: Relevance
“…Electrophoretically homogeneous IgGs from sera of SCZ patients and healthy donors were purified by affinity chromatography of serum proteins on protein G‐Sepharose and then by FPLC gel filtration under “acid shock” conditions as in . To analyze the “average” RNase activity of IgGs, we have prepared a mixture of equal amounts of 35 electrophoretically homogeneous IgGs of SCZ patients (scz‐IgG mix ) and 20 healthy donors (healt‐IgG mix ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrophoretically homogeneous IgGs from sera of SCZ patients and healthy donors were purified by affinity chromatography of serum proteins on protein G‐Sepharose and then by FPLC gel filtration under “acid shock” conditions as in . To analyze the “average” RNase activity of IgGs, we have prepared a mixture of equal amounts of 35 electrophoretically homogeneous IgGs of SCZ patients (scz‐IgG mix ) and 20 healthy donors (healt‐IgG mix ).…”
Section: Methodsmentioning
confidence: 99%
“…FPLC gel‐filtration of scz‐IgG mix under conditions of “acidic shock” (pH 2.6) and its affinity chromatography on Sepharose bearing immobilized mouse Abs against human IgGs were carried out as in Refs. .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, Ermakov et al reported DNA‐hydrolyzing activity of IgG antibodies in schizophrenic patients. Their results showed that the IgG antibodies with DNase activity were seen in 80% of patients with schizophrenia . Liu et al also studied serum immunoinflammation‐related protein complex changes in psychosis, and their major finding was that total serum amounts of IgG, IgA, and IgM were significantly lower in patients with schizophrenia .…”
mentioning
confidence: 99%
“…According to the previous studies, immune dysfunction may contribute to the pathogenesis of psychiatric diseases such as schizophrenia in the field of Neuroimmunology [6]. Overall, two general reasons can consider for positive lupus anticoagulant in the schizophrenia patients, firstly, brain inflammation as well as damage to the membrane of brain cells that can induce autoantibodies production [7], secondly, drug-induced lupus anticoagulant can be resulted from long term use of certain medications, such as phenothiazines. These findings trigger questions regarding what disorders can be result following the schizophrenia-induced autoimmunity.…”
Section: Introductionmentioning
confidence: 99%